Overlooked CO2 emissions induced by air pollution control devices in coal-fired power plants - Zhang, Pengfei; Feng, Kuishuang; Yan, Li; Guo, Yaqin; Gao, Bei; Li, Jiashuo (Environmental science and ecotechnology, 2024)
China's efforts to mitigate air pollution from its large-scale coal-fired power plants (CFPPs) have involved the widespread use of air pollution control devices (APCDs). However, the operation of these devices relies on substantial electricity generated by CFPPs, resulting in indirect CO2 emissions. The extent of CO2 emissions caused by APCDs in China remains uncertain. Here, using a plant-level dataset, we quantified the CO2 emissions associated with electricity consumption by APCDs in China's CFPPs. Our findings reveal a significant rise in CO2 emissions attributed to APCDs, increasing from 1.48 Mt in 2000 to 51.7 Mt in 2020. Moreover, the contribution of APCDs to total CO2 emissions from coal-fired power generation escalated from 0.12% to 1.19%. Among the APCDs, desulfurization devices accounted for approximately 80% of the CO2 emissions, followed by dust removal and denitration devices. Scenario analysis indicates that the lifespan of CFPPs will profoundly impact future emissions, with Nei Mongol, Shanxi, and Shandong provinces projected to exhibit the highest emissions. Our study emphasizes the urgent need for a comprehensive assessment of environmental policies and provides valuable insights for the integrated management of air pollutants and carbon emissions in CFPPs. [Display omitted] •CO2 emissions induced by air pollution control devices are quantified.•A plant-level CO2 emission inventory is compiled.•Future emissions under diverse climate targets are simulated.•Hotspots of future emissions are identified.